Manganese phytate graft modified MXene / carbon microsphere flame retardant and preparation method thereof
By grafting and modifying MXene with manganese phytate and combining it with carbon microspheres, the problems of low flame retardant efficiency and poor compatibility with PLA matrix in the field of flame retardant are solved, and the effect of significantly improving flame retardant performance and improving compatibility is achieved.
Patent Information
- Application Number
- CN202510073239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
As a separate flame retardant, MXene has low flame retardant efficiency and poor dispersion and interface compatibility with PLA substrates, which affects the mechanical properties and flame retardant properties of the composite materials.
MXene/carbon microsphere flame retardant was prepared by grafting and modifying MXene using manganese phytate using silane coupling agent APTES as the surface modification agent, and hydrothermal carbon microspheres were electrostatically assembled on the surface.
It significantly improves the flame retardant and smoke suppression performance, improves the hydrophobic performance and its compatibility with the PLA matrix, and improves the carbon-forming performance of the composite material, thereby greatly enhancing its flame retardant performance.
Smart Images

Figure CN119875205A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardancy, and specifically relates to a manganese phytate grafted modified MXene / carbon microsphere flame retardant and a preparation method thereof. Background Art
[0002] MXene was first discovered by Professor Yury Gogotsi and Professor Michel Barsoum of Drexel University in 2011. With its excellent conductivity, hydrophilicity and excellent mechanical properties, it quickly became a research hotspot in academia. As a two-dimensional layered nanomaterial, MXene has good thermal stability, unique layered structure, excellent catalytic activity and adjustable surface functional groups. Its unique two-dimensional structure and high specific surface area enable it to act as a physical barrier layer to effectively block heat transfer and delay thermal decomposition of the matrix. This physical barrier can form a protective layer on the surface of the material, reduce the transfer of heat and oxygen, and thus reduce the combustion rate of the material. Moreover, transition metal compounds such as TiO2 produced by MXene combustion have good catalytic activity, can promote the carbonization of the polymer matrix, help to form a stable carbon layer during the combustion process, reduce the release of combustible gases, and play a good catalytic carbonization and smoke suppression effect. In addition, the MXene surface has abundant functional groups, which makes it easier to modify, enhance its dispersibility and compatibility in composite materials, and thus improve the flame retardant effect. However, Ti3C2T x It also exhibits some inherent defects. For example, as a single flame retardant, its flame retardant efficiency is low. Moreover, MXene, like other layered nanomaterials, is easy to stack and aggregate. Its dispersibility and interfacial compatibility with the PLA matrix are poor, which affects the mechanical properties and flame retardant properties of the composite material. This seriously hinders its application in the flame retardant field. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a manganese phytate grafted modified MXene / carbon microsphere flame retardant and a preparation method thereof. By using the silane coupling agent APTES as a surface modifier, using manganese phytate to graft modify MXene and electrostatically self-assemble hydrothermal carbon microspheres on the surface, a manganese phytate grafted modified MXene / carbon microsphere flame retardant is successfully prepared, which not only significantly improves the flame retardant and smoke suppression performance, but also improves the hydrophobicity and its compatibility with the PLA matrix. At the same time, the charring performance of the composite material is greatly improved, which greatly enhances its flame retardant performance.
[0004] In order to achieve the above object, the present invention adopts the following technical solution:
[0005] A method for preparing a manganese phytate-grafted modified MXene / carbon microsphere flame retardant comprises the following steps:
[0006] (1) dissolving chitosan powder in acetic acid solution, performing a hydrothermal reaction, separating the solid from the liquid, and grinding the mixture into powder to obtain carbon microspheres (CMSs);
[0007] (2) ultrasonically dispersing MXene in deionized water to obtain a MXene dispersion; adding APTES (3-aminopropyltriethoxysilane) to the MXene dispersion, stirring and mixing thoroughly, and obtaining silanized MXene after solid-liquid separation;
[0008] (3) The silanized MXene was ultrasonically dispersed in deionized water. After ultrasonic treatment in an ice bath, PA (phytic acid) and manganese acetate were added in sequence and stirred thoroughly to obtain phytic acid manganese grafted modified MXene, which was recorded as MXene-PAMn.
[0009] (4) CMSs and MXene-PAMn were ultrasonically dispersed in deionized water to obtain a mixed slurry, which was fully stirred and reacted under a nitrogen atmosphere. The solid sample obtained after solid-liquid separation was calcined to obtain a phytic acid manganese grafted modified MXene / carbon microsphere flame retardant, which was recorded as MXene-PAMn / CMSs.
[0010] Those skilled in the art know that MXene, as a two-dimensional layered nanomaterial, has a unique layered structure and high specific surface area, which enables it to act as a physical barrier layer to effectively block heat transfer and delay thermal decomposition of the matrix, and the transition metal compounds in MXene have good catalytic activity, which plays a good role in catalytic carbonization and smoke suppression. However, MXene, like other layered nanomaterials, has the characteristics of easy stacking and aggregation, and has poor dispersibility and interfacial compatibility with the PLA matrix, which affects the mechanical properties and flame retardant properties of the composite material.
[0011] In view of this, the present invention uses silane coupling agent (3-aminopropyl) triethoxysilane (APTES) as a surface modifier, PA and CMSs as flame retardant synergists, and the silanol group in APTES undergoes a condensation reaction with the hydroxyl group on the surface of MXene to form a Ti-O-Si bond. Then, the surface of the MXene nanosheet is grafted with phytic acid molecules through the silane coupling method to chelate Mn 2+, a bio-based organic / inorganic hybrid MXene-based flame retardant containing N / P was prepared, in which the physical barrier effect of the evenly dispersed flame retardant and the nitrogen-phosphorus synergistic flame retardant system promoted the cross-linking of the carbon layer and the synergistic catalytic carbonization of the transition metal elements Ti and Mn formed dense and stable char to block heat and oxygen transfer, reduce smoke release, and significantly improve the flame retardant and smoke suppression properties; phytic acid releases phosphorus-containing free radicals PO· when thermally cracked, which captures HO· and H· in the air, interrupts the combustion chain reaction, and thus reduces the combustion rate; PA grafting and silane coupling to introduce long carbon chains significantly improve the hydrophobicity of the flame retardant, reduce the agglomeration and stacking phenomenon of the flame retardant in the PLA matrix, and improve the dispersibility of the flame retardant in the PLA matrix.
[0012] Preferably, in step (1), the temperature of the hydrothermal reaction is 160 to 200° C. and the time is 8 to 24 hours.
[0013] Preferably, in step (2), the concentration of the MXene dispersion is 0.2-0.5 g:100 ml.
[0014] Preferably, in step (2), the mass volume ratio of MXene and APTES is 1 g: 30-50 ml.
[0015] Preferably, in step (3), the amount of silylated MXene, PA and manganese acetate used is 1 g: 1-3 ml: 0.3-0.6 g.
[0016] Preferably, in step (4), the mass ratio of CMSs to MXene-PAMn is 2:1.
[0017] Preferably, in step (4), the calcination temperature is 150-200° C. and the calcination time is 0.5-2 h.
[0018] The present invention also provides a manganese phytate grafted modified MXene / carbon microsphere flame retardant prepared by the above preparation method.
[0019] The advantages of the present invention are:
[0020] (1) The present invention uses silane coupling agent APTES as a surface modifier, uses manganese phytate to graft-modify MXene, and electrostatically self-assembles hydrothermal carbon microspheres on the surface to successfully prepare manganese phytate grafted modified MXene / carbon microsphere flame retardant, wherein the physical barrier effect of the uniformly dispersed flame retardant and the nitrogen-phosphorus synergistic flame retardant system play a role in promoting the cross-linking of the carbon layer and the synergistic catalytic carbonization effect of the transition metal elements Ti and Mn, forming dense and stable coke to block heat and oxygen transfer and reduce smoke release; in addition, phytic acid releases phosphorus-containing free radicals PO· when thermally cracked, which interrupt the combustion chain reaction by capturing HO· and H· in the air, thereby reducing the combustion rate;
[0021] (2) The present invention introduces a long carbon chain through PA grafting and silane coupling, which gives the flame retardant a rough surface and a larger interlayer spacing without destroying the special layered structure, significantly improves the hydrophobicity of the flame retardant, reduces the agglomeration and stacking phenomenon of the flame retardant in the PLA matrix, and improves the dispersibility of the flame retardant in the PLA matrix.
[0022] In summary, the present invention successfully prepared the manganese phytate grafted modified MXene / carbon microsphere flame retardant by using the silane coupling agent APTES as a surface modifier, using manganese phytate to graft modify MXene and loading hydrothermal carbon microspheres on the surface. The flame retardant and smoke suppression performance can be significantly improved, and the hydrophobic performance and compatibility with the PLA matrix can be improved. At the same time, the carbonization performance of the composite material is greatly improved, which greatly enhances its flame retardant performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 are XRD patterns of MXene, MXene / CMSs prepared in Comparative Example 1, and MXene-PAMn / CMSs prepared in Example 1;
[0024] like Figure 1 As shown in the figure, the XRD spectrum of MXene shows characteristic diffraction peaks at 2θ=8.9°(002), 16.3°(004), 27.4°(008), and 34.1°(110), which are sharp and strong and correspond to the standard card of titanium carbide aluminum (JCPDS52-0875). In addition to the peaks of (002), (004), (008), and (110), the XRD spectrum of MXene / CMSs and MXene-PAMn / CMSs also shows a characteristic peak corresponding to the graphite surface in carbon microspheres near 2θ=21.8°. Compared with MXene / CMSs, the (002) position in the XRD spectrum of MXene-PAMn / CMSs shifts to a smaller angle, with 2θ=5.7° reduced to 5.4°, and the interplanar spacing calculated by the Bragg equation 2dsinθ=nλ increased from d(002)=0.78nm to 0.82nm, indicating that the interlayer spacing of MXene-PAMn / CMSs nanosheets after grafting with phytic acid is further increased on the basis of MXene / CMSs.
[0025] Figure 2 FT-IR images of MXene, MXene / CMSs prepared in Comparative Example 1, and MXene-PAMn / CMSs prepared in Example 1;
[0026] like Figure 2 As shown in the infrared spectrum of MXene, the -1The broad vibration peak at 2921cm corresponds to the stretching vibration of the hydroxyl group (ν-OH) on the MXene surface. -1 、1630cm -1 and 1440cm -1 The characteristic absorption peaks at 655 cm-1 correspond to the stretching vibrations of CH, -CH and C=O bonds. -1 The characteristic peak at 1154 cm corresponds to the stretching vibration of the Ti-O bond. Compared with the FT-IR spectrum of MXene, the infrared spectrum of MXene / CMSs not only has the above characteristic peaks of MXene, but also can observe the peak at 1154 cm -1 In addition, by analyzing the infrared spectrum of MXene-PAMn / CMSs, it can be seen that the peaks of the CN bond stretching vibration in 3400-3500cm -1 The broad vibration peak at 1113 cm is attributed to the stretching vibration of the hydroxyl group in MXene-PAMn / CMSs. In addition to the characteristic absorption peaks of MXene and CMSs, such as CH, C=O, CN and Ti-O bonds, the infrared spectrum of MXene-PAMn / CMSs also has new characteristic peaks: at 1113 cm -1 、1097cm -1 and 760cm -1 The characteristic absorption peaks at correspond to P=O, PO and P-OH in the PA molecular structure, proving the existence of phytic acid. Combined with the XRD analysis results, infrared spectroscopy analysis further proved that the organic / inorganic hybrid flame retardant MXene-PAMn / CMSs containing N / P was prepared by grafting modification.
[0027] Figure 3 These are SEM and TEM images of MXene, MXene / CMSs prepared in Comparative Example 1, and MXene-PAMn / CMSs prepared in Example 1;
[0028] like Figure 3As shown in the figure, a typical two-dimensional layered nanosheet structure can be observed in the SEM image (A) and TEM image (F) of MXene, and there are ripples and wrinkles on the surface, indicating that the nanosheets are stacked and agglomerated with each other. According to the SEM image (B) of MXene-PAMn, the surface of the nanosheet is covered with uniformly distributed nanoparticles, which is due to the grafting of PAMn to the surface of silanized MXene, and the modified MXene-PAMn still maintains a two-dimensional layered structure. For MXene-PAMn / CMSs, uniformly distributed nanoparticles and spherical structures can be observed on the surface of the nanosheet in the SEM images (C and D) and TEM images (G, H and I), corresponding to the PAMn and CMSs components in the system, respectively. Compared with the relatively smooth surface of MXene, the surfaces of MXene-PAMn and MXene-PAMn / CMSs become very rough due to the grafting of phytic acid and the loading of CMSs, and the specific surface area increases, which is conducive to enhancing the interfacial interaction between the flame retardant and the matrix material, thereby promoting dispersion and compatibility. From the EDS mapping results (E) of MXene-PAMn / CMSs, it can be seen that MXene-PAMn / CMSs contains elements such as C, N, O, Ti, P, and Mn. Among them, the P and Mn elements further confirm the grafting modification of PAMn on MXene, and the N element comes from the chitosan carbon microspheres loaded on the surface. From the above analysis, it can be concluded that the flame retardant is given a rough surface and a larger interlayer spacing without destroying the special layered structure through grafting modification and silanization, which is conducive to dispersion in PLA. The successful modification of MXene by PA and CMSs constructs a multi-component N / P synergistic flame retardant system, and introduces transition metals Ti and Mn.
[0029] Figure 4 TG (A) and DTG (B) graphs of MXene, MXene / CMSs prepared in Comparative Example 1, and MXene-PAMn / CMSs prepared in Example 1;
[0030] like Figure 4 As shown, the TG curve of MXene shows that there are three thermal weight loss stages between 30℃ and 800℃: the first thermal weight loss stage is before 120℃, and this process is mainly the removal of physically adsorbed water on the MXene surface. The second thermal weight loss stage occurs between 160℃ and 300℃, and this process mainly involves the thermal decomposition of functional groups on the MXene surface, such as the decomposition of hydroxyl groups. The third stage of the thermal weight loss process is between 600 and 800℃, which is attributed to the oxidation of Ti to form TiO2, and the transformation of layered MXene into anatase. The total thermal weight loss of MXene is 13.8%, and the initial decomposition temperature (T 5%) is 163.1℃. The thermal decomposition process of MXene / CMSs and MXene-PAMn / CMSs is similar to that of MXene, but the decomposition temperature has increased to varying degrees, indicating that the thermal stability has been enhanced. For MXene-PAMn / CMSs, the first thermal weight loss stage also occurred before 120℃, while the second thermal weight loss peak was around 581.5℃. During this stage, the decomposition and carbonization of MXene mainly occurred. The thermal weight loss of MXene-PAMn / CMSs was only 5.8%, which was 8% and 10.2% lower than that of MXene (13.8%) and MXene / CMSs (16%), respectively. 5% It is 590.5℃, which is 423.9℃ higher than that of MXene, and the thermal weight loss curve becomes smoother, indicating that the introduction of grafted phytic acid can enhance the heat resistance of the flame retardant. The significantly improved thermal stability and residual rate are mainly due to the synergy of nitrogen and phosphorus after PAMn grafting and the catalytic carbonization of manganese elements. Therefore, MXene-PAMn / CMSs can better play a physical barrier role at high temperatures, protect the further thermal decomposition of the bottom PLA matrix to inhibit combustion, and enable it to better play a flame retardant effect.
[0031] Figure 5 MXene, MXene / CMSs prepared in Comparative Example 1, and MXene-PAMn / CMSs prepared in Example 1 are water contact angle diagrams;
[0032] like Figure 5 As shown in the figure, in general, the lower the WCA value of a material, the stronger its hydrophilicity, and the higher the WCA value, the stronger its hydrophobicity; the water contact angle of MXene is 7.8°, while the water contact angle of MXene / CMSs is increased to 49.5°. The water contact angle of MXene is extremely low, indicating that MXene is a material with extremely poor hydrophobicity, while the water contact angle of MXene / CMSs flame retardant has increased significantly, indicating that its hydrophobicity has been significantly improved, because after the CMSs are uniformly loaded on the surface, the contact area of MXene / CMSs nanosheets is expanded, which is conducive to the dispersion and compatibility of the flame retardant. It is worth noting that the water contact angle of MXene-PAMn / CMSs flame retardant is further increased to 54.4°, not only because of the enlarged specific surface area, but also mostly because the phytic acid grafted and silanized MXene replaces the hydrophilic groups (-OH, etc.) on the surface with hydrophobic long carbon chains. The improvement of the hydrophobicity of the MXene-PAMn / CMSs flame retardant after grafting modification is beneficial to improving the dispersibility and compatibility between the nanosheets and the matrix during the melt processing of the composite material, thereby enhancing the mechanical properties of the PLA composite material and the density and quality of the carbon layer generated after combustion, thereby significantly improving the flame retardant properties of PLA.
[0033] Figure 6It is the cross-sectional SEM images of pure PLA and PLA / MXene and PLA / MXene-PAMn / CMSs composites prepared by melt blending of MXene and MXene-PAMn / CMSs, respectively;
[0034] like Figure 6 As shown in the figure, the microstructures of the liquid nitrogen brittle fracture sections of pure PLA, PLA / MXene and PLA / MXene-PAMn / CMSs composites are compared. The fracture section of pure PLA is relatively smooth with a small number of cracks, which is the stress result during liquid nitrogen brittle fracture. By observing the micromorphology of the fracture section of PLA / MXene composites through SEM, it can be seen that the cross section is uneven and due to the agglomeration of layered MXene nanosheets, the flame retardant filler is scattered and disorderly accumulated in the PLA matrix, presenting an irregular block structure of varying sizes, indicating poor dispersion. Moreover, the interface between MXene and PLA matrix is obvious, and MXene nanosheets are unevenly distributed and embedded in PLA, resulting in holes and defects in the composite material, indicating that the interface compatibility between MXene and PLA is poor, which is bound to have a negative impact on mechanical properties and flame retardancy. By observing the SEM image of the fractured cross section of the PLA / MXene-PAMn / CMSs composite material, it can be seen that the spherical structure similar to CMSs and the layered structure of MXene nanosheets, the stacking and agglomeration phenomenon between flame retardants is reduced and the edges are very blurred, and the interface between the flame retardant additive and the matrix is almost not observed, and the two seem to be fused together. PA grafted MXene / CMSs reduces the mutual stacking and agglomeration between nanosheets, and promotes the compatibility and dispersibility of MXene-PAMn / CMSs flame retardant and PLA, which is consistent with the WCA analysis. At the same time, the improvement of dispersibility and compatibility will enhance the mechanical properties of melt-processed PLA / MXene-PAMn / CMSs composite materials and the uniform density and quality of the carbon layer formed by combustion, thereby improving the fire retardant properties.
[0035] Figure 7 These are digital photos and SEM images of carbon residues of pure PLA and PLA / MXene and PLA / MXene-PAMn / CMSs composites prepared by melt blending of MXene and MXene-PAMn / CMSs respectively after CCT testing;
[0036] like Figure 7As shown in the figure, the digital photo of the residual carbon shows that there is almost no residual coke after the combustion of PLA; while the residual carbon after the combustion of PLA / MXene composite material is very loose, with low density and carbon yield, and there are honeycomb holes on the surface of the carbon layer and white matter on the surface, indicating that MXene is oxidized to rutile in the air during combustion, and the loose carbon layer cannot show the ideal flame retardant and smoke suppression efficiency; the carbon layer of PLA / MXene-PAMn / CMSs composite material is denser, and the thickness and carbonization rate are also significantly improved. The SEM image shows that the residual carbon after pure PLA is burned is very thin and cannot play a physical barrier role during the combustion process; the SEM image of the residual carbon after combustion of the PLA / MXene composite material shows anatase structure after MXene oxidation, and the scattered and disordered accumulation forms a carbon layer. This is because the extremely poor dispersibility and compatibility of MXene in the PLA matrix makes the carbon layer uneven and not dense. This carbon layer also cannot play a good physical barrier role and cannot effectively suppress the release of heat and toxic smoke; the SEM image of the residual carbon of the PLA / MXene-PAMn / CMSs composite material shows that its carbon layer structure is continuous and evenly distributed. The synergistic catalytic carbonization of titanium and manganese makes the transition metal oxide and the carbon layer tightly stacked to form a stable and dense barrier. The dense carbon layer formed by the composite material during combustion blocks heat exchange and oxygen, blocks the escape of combustion smoke, and inhibits further combustion of the PLA matrix, which significantly improves the flame retardant and smoke suppression properties of the PLA composite material. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with embodiments.
[0038] MXene is obtained by etching Ti3AlC2:
[0039] First, 1g of Ti3AlC2 powder was slowly added to a plastic beaker containing 20mL of 50% pure HF solution using a plastic medicine spoon and magnetically stirred at room temperature for 24h. Subsequently, the reacted solution was centrifuged several times at 5000rpm until the pH of the suspension was >6. After adding a certain amount of deionized water and ultrasonicating for 20min, the obtained solid was washed with deionized water and filtered. Finally, the solid obtained after filtration was dried at 80°C for 8h and then ground to obtain MXene powder and sealed for storage.
[0040] Example 1
[0041] (1) Use phytic acid (PA) and silane coupling agent 3-aminopropyltriethoxysilane (APTES) to graft and modify MXene: weigh 1 g of the prepared MXene and dissolve it in 300 mL of deionized water. Ice bath ultrasonication for 30 min makes it evenly dispersed. Then, 40 mL of 1% APTES solution is added dropwise. After magnetic stirring for 1 h, the reaction is centrifuged, washed and dried to obtain silanized MXene. Then, 1 g of silanized MXene sample was ultrasonically dispersed in 300 mL of deionized water. After ultrasonic treatment in an ice bath for 30 min, 2 mL of 70% PA solution was accurately measured with a pipette and added to 50 mL of deionized water. The diluted PA solution was slowly added dropwise to the reaction system, and then 0.5 g of manganese acetate was weighed and dissolved in 50 mL of deionized water to prepare a solution, which was then added dropwise to the above reaction system. After magnetic stirring for 30 min, the reaction was completed, filtered and washed with a filter membrane to remove the remaining reactants, and dried in vacuo at 80 ° C for 12 h to obtain phytic acid manganese grafted modified MXene, recorded as MXene-PAMn.
[0042] (2) Weigh 2g CMSs and 1g MXene-PAMn and disperse them in 50mL deionized water, and disperse them evenly by ultrasound. Then transfer the liquid to a three-necked flask and place it in a constant temperature magnetic stirrer. React for 1.5h under a nitrogen atmosphere. Filter, wash and dry the slurry after the reaction. In the second step, place the sample in a quartz boat and calcine it at 180°C for 1h in a nitrogen atmosphere using a tube furnace. After the reaction is cooled to room temperature, wash the obtained product with 0.1M HCl and deionized water, and filter and dry to obtain a phytic acid manganese grafted modified MXene / carbon microsphere flame retardant, recorded as MXene-PAMn / CMSs.
[0043] Comparative Example 1
[0044] Weigh 2g CMSs and 1g MXene and disperse them in 50mL deionized water, and disperse them evenly by ultrasound. Then transfer the liquid to a three-necked flask and place it in a constant temperature magnetic stirrer. React for 1.5h under a nitrogen atmosphere. Filter, wash and dry the slurry after the reaction. In the second step, place the sample in a quartz boat and calcine it at 180°C for 1h in a nitrogen atmosphere using a tube furnace. After the reaction is cooled to room temperature, wash the obtained product with 0.1M HCl and deionized water, and filter and dry to obtain chitosan carbon microsphere modified MXene flame retardant, which is recorded as MXene / CMSs.
[0045] Performance Testing:
[0046] By melt blending, MXene (D1), MXene / CMSs (D2) and MXene-PAMn / CMSs (S1) flame retardants were melt blended with PLA to prepare PLA composite materials with a flame retardant mass fraction of 5 wt%. The flame retardant and mechanical properties of the composite materials were tested. The results are shown in Table 1.
[0047] Table 1 Flame retardant and mechanical properties test results of different PLA composites
[0048]
[0049] As shown in Table 1, the tensile strength and elongation at break of pure PLA are 52.7 MPa and 5.4%, respectively, showing good elasticity and toughness. With the addition of flame retardants, the tensile strength and elongation at break of the composite material decreased to varying degrees. When 5wt% MXene was added, the tensile strength and elongation at break of PLA / MXene were 48.8 MPa and 1.7%, respectively, and its mechanical properties decreased to a large extent. When 5wt% MXene-PAMn / CMSs was added, the mechanical properties were significantly improved, and its tensile strength and elongation at break were 50.7 MPa and 2.9%, respectively.
[0050] Pure PLA is extremely flammable and has a melting droplet phenomenon in the combustion experiment. Its LOI value is only 19.2. When 5wt% MXene is added, the LOI value is 20.9%, which only passes the UL-94V-2 level. When 5wt% MXene-PAMn / CMSs is added, the LOI is directly increased to 27.5%, and it reaches the UL-94V-0 level, showing good flame retardant properties.
[0051] The pHRR (peak heat release rate) of pure PLA is 446.4 kW·m -2 , which makes it very easy to burn in the air. After adding different flame retardants, the pHRR of PLA / MXene decreased to 358.4kW·m -2 , while the pHRR of PLA / MXene-PAMn / CMSs composite material further decreased to 310.2kW·m -2 The THR (total heat release) of pure PLA is 74.9 MJ·m -2 The THR of PLA / MXene is 68.4 MJ·m -2 , while that of PLA / MXene-PAMn / CMSs composite material was reduced to 61.6 MJ·m -2 It can be seen that MXene-PAMn / CMSs can significantly improve the flame retardant properties of PLA.
[0052] The toxic smoke released by polymers during combustion is the main cause of most deaths in fires, so it is of great significance to study the smoke suppression performance of polymers. Pure PLA will release a large amount of smoke during combustion, and its TSP (total smoke generation) is 24.64m 2 When 5 wt% MXene was added, the TSP of the PLA / MXene composite dropped to 19.08 m 2 After adding MXene-PAMn / CMSs flame retardant to PLA, the TSP of PLA / MXene-PAMn / CMSs composite material dropped to 15.43m 2 The smoke release during the combustion process has been significantly controlled and its smoke suppression performance has been significantly improved.
Claims
1. A method for preparing a manganese phytate-grafted modified MXene / carbon microsphere flame retardant, characterized in that: The following steps are involved: (1) dissolving chitosan powder in acetic acid solution, performing a hydrothermal reaction, separating the solid from the liquid, and grinding the mixture into powder to obtain carbon microspheres (CMSs); (2) ultrasonically dispersing MXene in deionized water to obtain a MXene dispersion; adding 3-aminopropyltriethoxysilane to the MXene dispersion, stirring and mixing, and obtaining silanized MXene after solid-liquid separation; (3) The silanized MXene was ultrasonically dispersed in deionized water. After ultrasonic treatment in an ice bath, phytic acid and manganese acetate were added in sequence and stirred thoroughly to obtain phytic acid manganese grafted modified MXene, which was recorded as MXene-PAMn. (4) CMSs and MXene-PAMn were ultrasonically dispersed in deionized water to obtain a mixed slurry, which was fully stirred and reacted under a nitrogen atmosphere. The solid sample obtained after solid-liquid separation was calcined to obtain a phytic acid manganese grafted modified MXene / carbon microsphere flame retardant, which was recorded as MXene-PAMn / CMSs.
2. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 160 to 200° C. and the time is 8 to 24 hours.
3. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the MXene dispersion is 0.2-0.5 g:100 ml.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass volume ratio of MXene and 3-aminopropyltriethoxysilane is 1 g: 30-50 ml.
5. The preparation method according to claim 1, characterized in that: In step (3), the amount of silanized MXene, phytic acid and manganese acetate is 1g: 1-3ml: 0.3-0.6g.
6. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of CMSs to MXene-PAMn is 2:
1.
7. The preparation method according to claim 1, characterized in that: In step (4), the calcination temperature is 150-200° C. and the calcination time is 0.5-2 h.
8. A phytic acid manganese grafted modified MXene / carbon microsphere flame retardant prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of ammonium polyphosphate cladded microsphere flame retardant
CN109181248A
MXene nanosheet with free radical capturing function as well as preparation method and application of MXene nanosheet
CN114314591A
Nitrogen-phosphorus high-synergism bifunctional flame retardant, efficient flame-retardant beta-crystal polypropylene material as well as preparation method and application of efficient flame-retardant beta-crystal polypropylene material
CN116554549A
Preparation method and application of phytate carbon microsphere flame retardant
CN118085411A
High speed deposition method of eco-retardant for anti-flammable polyurethane foam and eco-friendly flame-retardant polyurethane foam manufactured thereby
KR102407198B1